Cutaneous extranodal NK/T‐cell lymphoma mimicking cellulitis an HIV positive patient without lymphopenia. (2nd February 2017) - Malviya, Neeta; Rainwater, Yevgeniya B.; Vandergriff, Travis; Mauskar, Melissa M.
Abstract : We present the case of a 28‐year‐old male with a history of human immunodeficiency virus (HIV) with a 1‐month history of a steadily enlarging, firm painful lesion on the right posterior shoulder. The patient was initially treated for cellulitis given his clinical picture. Histopathologic examination revealed an angiocentric and dermal proliferation of markedly atypical lymphoid cells with numerous mitoses and apoptotic bodies along with broad zones of necrosis. Biopsy revealed the presentation to be consistent with NK/T‐cell lymphoma. The cutaneous lesions from NK/T‐cell lymphoma can often be initially mistaken for cellulitis, therefore this malignancy should be included on the differential in a patient HIV/acquired immune deficiency syndrome (AIDS).